A control scheme to enhance low voltage ride‐through of brushless doubly‐fed induction generators. Issue 9 (24th November 2015) - Tohidi, S.; Oraee, H.; Zolghadri, M. R.; Rahimi, M.
Abstract: The use of brushless doubly‐fed induction generator has been recently proposed for wind turbines because of its variable speed operation with fractional size converter without the need to brush and slip ring. This paper introduces a control scheme to improve low voltage ride‐through capability of doubly‐fed induction generator considering grid code requirements. The proposed control strategy is based on analysis of flux linkages and back electromotive forces and intends to retain the control‐winding current below the safety limit (typically 2 pu) during severe voltage dips. The time‐domain simulations validate effectiveness of the proposed scheme to protect the converter against failure as well as support reactive power required by German grid code. Copyright © 2015 John Wiley & Sons, Ltd.